2022
DOI: 10.1002/jcp.30727
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of sodium‐glucose co‐transporter 2 inhibitors in attenuating cardiac arrhythmias in diabetes and heart failure

Abstract: Sodium-glucose co-transporter 2 (SGLT-2) inhibitors are antidiabetic drugs that have been shown to exert cardiovascular benefits. Their benefits including a reduction of cardiovascular events and worsening heart failure have been extended to nondiabetic patients with high-risk. Although both heart failure and diabetes are known to increase risk of cardiac arrhythmias, the effects of SGLT-2 inhibitors on arrhythmia reduction and their underlying mechanisms are still not fully understood. This review aims to sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In addition, SGLT2i also has anti-inflammatory and antiarrhythmic properties in patients with acute coronary syndrome, stable ischemic heart disease, multi-vessel coronary stenosis, and can significantly reduce in-hospital arrhythmic burden in treated patients [ 30 , 31 , 32 , 33 ]. For cardiac arrhythmias, SGLT2i have multiple antiarrhythmic mechanisms, which include: (1) osmotic diuresis to lower blood glucose and reduce cardiac load: both the osmotic effect of glucose and natriuresis contribute to the diuretic effect of SGLT2i, resulting in plasma volume contraction, which hemodynamically unload the left ventricle, decreases myocardial oxygen consumption, filling pressure, and ventricular wall tension [ 34 ]; (2) regulation of cardiac ion balance: SGLT2i can affect a variety of cardiac ion currents to attenuate action potential duration prolongation and reduce the development of calcium-related cardiac arrhythmias by affecting calcium homeostasis and calcium ion current [ 12 ]; (3) regulation of mitochondrial function and improvement of myocardial remodeling: SGLT2i can increases mitochondrial calcium uptake and mitigate mitochondrial swelling in cardiomyocytes, thereby restoring the antioxidant capacity of mitochondria and exerting antiarrhythmic effects [ 35 ]; and (4) inhibition of sympathetic activity: SGLT2i may reduce the risk of arrhythmias by inhibiting levels of markers of the sympathetic nervous system (norepinephrine and tyrosine hydroxylase), attenuating the stimulation of afferent sympathetic activity, and reducing the activity of sympathetic nervous system [ 36 ]. Additionally, SGLT2i can reduce cardiac inflammation, myocardial oxygen consumption, and oxidative stress, all of which may contribute to reducing the risk of cardiac arrhythmias [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SGLT2i also has anti-inflammatory and antiarrhythmic properties in patients with acute coronary syndrome, stable ischemic heart disease, multi-vessel coronary stenosis, and can significantly reduce in-hospital arrhythmic burden in treated patients [ 30 , 31 , 32 , 33 ]. For cardiac arrhythmias, SGLT2i have multiple antiarrhythmic mechanisms, which include: (1) osmotic diuresis to lower blood glucose and reduce cardiac load: both the osmotic effect of glucose and natriuresis contribute to the diuretic effect of SGLT2i, resulting in plasma volume contraction, which hemodynamically unload the left ventricle, decreases myocardial oxygen consumption, filling pressure, and ventricular wall tension [ 34 ]; (2) regulation of cardiac ion balance: SGLT2i can affect a variety of cardiac ion currents to attenuate action potential duration prolongation and reduce the development of calcium-related cardiac arrhythmias by affecting calcium homeostasis and calcium ion current [ 12 ]; (3) regulation of mitochondrial function and improvement of myocardial remodeling: SGLT2i can increases mitochondrial calcium uptake and mitigate mitochondrial swelling in cardiomyocytes, thereby restoring the antioxidant capacity of mitochondria and exerting antiarrhythmic effects [ 35 ]; and (4) inhibition of sympathetic activity: SGLT2i may reduce the risk of arrhythmias by inhibiting levels of markers of the sympathetic nervous system (norepinephrine and tyrosine hydroxylase), attenuating the stimulation of afferent sympathetic activity, and reducing the activity of sympathetic nervous system [ 36 ]. Additionally, SGLT2i can reduce cardiac inflammation, myocardial oxygen consumption, and oxidative stress, all of which may contribute to reducing the risk of cardiac arrhythmias [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…CKD can also lead to increased cardiovascular risk such as cardiac arrhythmias and HF [ 11 ]. The present study identified potential antiarrhythmic benefits of SGLT2i, which can reduce cardiac arrhythmias by affecting cellular calcium ion current, calcium homeostasis, and reducing oxidative stress [ 12 ]. Therefore, the aim of this meta-analysis and systematic review was to gather the study results from all large CVOTs with SGLT2i to evaluate the effect of SGLT2i on common cardiac arrhythmia outcomes (tachycardia, SVT, VA, cardiac arrest, and bradyarrhythmia) in patients with T2DM, HF, and CKD.…”
Section: Introductionmentioning
confidence: 99%